POLICY INSTRUMENTS FOR REDUCING REGIONAL INCOME INEQUALITY IN UZBEKISTAN: EVIDENCE FROM PANEL AND SPATIAL ECONOMETRIC ANALYSIS - Muhammadkhon Muydinov (Modern American Journals, 2025)
Regional income inequality remains a persistent challenge in Uzbekistan despite recent economic growth and structural reforms. Significant disparities between regions undermine inclusive development, social cohesion, and long-term economic sustainability. This study examines the effectiveness of key policy instruments aimed at reducing regional income inequality in Uzbekistan using panel and spatial econometric methods. Based on regional data covering the period 2010–2023, the analysis evaluates the impact of fiscal transfers, infrastructure investment, human capital development, and entrepreneurship support on interregional income disparities. Fixed-effects panel regression and spatial autoregressive models reveal that infrastructure investment and human capital expenditures exert a statistically significant equalizing effect on regional incomes, while fiscal transfers primarily mitigate short-term imbalances without fostering long-term convergence. The findings suggest that development-oriented and spatially targeted policy instruments are more effective than compensatory mechanisms. The study contributes to the literature on regional inequality in transition economies and provides policy-relevant insights for balanced territorial development in Uzbekistan.
Keywords: Regional income inequality, policy instruments, panel data, spatial econometrics, Uzbekistan